(untitled) (Fiep Bulletin - online, 2012)
The Physical Education course curriculum goes through many changes and its guidelines since their emergence, related to the needs of society and changes in the labor market. The study aimed to verify the prospect of graduateds in Physical Education about the preparations provided by their professional training course. The research conducted with ten (10) graduates from the Physical Education in a particular institution in the outskirts of the city of São Paulo. The interview was semi-structured questionnaire and were analyzed by the methodology of content analysis. Respondents were satisfied with the quality of the course, faculty, programs offered by the institution and infrastructure, in addition to assessing reflective practitioners, able to develop intervention planning ethical and efficient. However they have grievances they aim changes to improvement for the quality of the course. According to the interviewees, they fit the job profile offered by the institution and presents features and knowledge built during the formation.